The attitude towards physical education of the high school students of the University of the Philippines College Cebu, 1975-1976 - Gallenero, Louisa Delgado 1938- (1977)
The aim of the study was to determine the students' attitude towards physical education. The instruments used in the study were the Wear Physical Education Scale Short Form, SRA Verbal, Subject Grade Average or Academic Achievement, and statistical treatment. The study showed that the attitude of the students of UP College Cebu High School towards physical education for the school year 1975-1976 was generally favorable or positive.
Appendices: leaves 79-91
Includes tables
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Vita
Keywords: University of the Philippines (Cebu City) -- Students; Physical education and training -- Philippines -- Cebu City; High school students -- Attitudes. -- Philippines -- Cebu City